Functional capacity associated with work ability in older university staff employed by the state - Juleimar Soares Coelho de Amorim; Celita Salmaso Trelha
Abstract Introduction: The increase in numbers of older adults in the workplace and in the number of years they spend in work prior to retiring has challenged health professionals to provide enable health conditions such that they may undertake occupational activity. Objective: To analyze the variables for functional ability, associated with work ability, in older adults who were government employees at a university. Methods: A cross-sectional design, with older workers aged 60 years old or over, located in different university centers and departments. A structured sociodemographic questionnaire was used to characterize the sample, and the Work Ability Index was used as an outcome variable for the associations, using the Timed Up and Go test, the handgrip strength test, the walking speed test and the chair sit to stand test. The Chi-squared test and Pearson correlation coefficient were used in the statistical analysis. The association of the factors of functional capacity was based on the odds ratio and 95% confidence interval, calculated using the Logistic Regression Model, as part of the SPSS statistical package for Windows. Results: A total of 258 staff participated in the investigation, with men (57.7%) and a lower age range (60 to 62 years old) predominating. Women differed in relation to falls after the age of 60 (p = 0.007) and in the last 12 months (p = 0.017). The mean Work Ability Index was 39.70 ± 5.64 points and a statistical association was ascertained between performance in the chair sit to stand test (OR = 2.26; p = 0.043). Muscle strength (r = 0.72; p < 0.000) and the chair sit to stand test (r = 0.73; p < 0.000) showed excellent correlation with work ability. Conclusion: The variables for functional capacity were associated with work ability.